Mentransformasi Hubungan Guru dan Siswa melalui Filosofi Montessori: Mengatasi Tantangan Pendidikan dan Meningkatkan Lingkungan Belajar - Faisal Reza Saputra (At Turots: Jurnal Pendidikan Islam, 2025)
This study examines the transformative potential of Montessori educational philosophy in reshaping teacher-student relationships and promoting holistic child development. Contemporary educational paradigms increasingly emphasize active student engagement and collaborative teacher-student dynamics, with the Montessori method emerging as a particularly innovative approach. Developed by Dr. Maria Montessori in the early 20th century, this child-centered pedagogy emphasizes learner autonomy, self-directed exploration, and the innate capacity of children to construct their own knowledge within carefully prepared environments. The research addresses critical challenges prevalent in traditional education systems, including ineffective teacher-student communication, low student engagement, insufficient social-emotional support and excessive academic pressure leading to stress and behavioral issues. Through philosophical analysis and comprehensive literature review, this investigation demonstrates how core Montessori principles—including prepared environments, self-directed learning, and mutual respect—can effectively address these systemic challenges. The study's objective include: (1) Identifying the fundamental concepts of Montessori philosophy, (2) Analyzing the main challenges in teacher-student relationships within traditional education systems, (3) Explaining the rationale for selecting Montessori philosophy as the theoretical framework, (4) Exploring how Montessori principles can address teacher-student relationship issues, and (5) Proposing Montessori-based solutions to improve teacher-student relationships. The research concludes with practical recommendations for integrating Montessori principles into mainstream education include: (1) Enhanced communication, (2) Increased student engagement, (3) Improved Social-Emotional Development, (4) Reduced Academic Stress. These proposals aim to create more nurturing educational ecosystems that foster authentic communication, meaningful student engagement, and reduced academic stress. By implementing Montessori-inspired reforms, educational institutions can develop learning environments that not only enhance cognitive outcomes but also support emotional well-being and social development, ultimately preparing students to thrive as confident, self-motivated learners. The study's findings have significant implications for policymakers, school administrators, and teacher educators seeking research-based approaches to improve teacher-student relationships and overall educational quality.